Effect of autologous NK cell immunotherapy on advanced lung adenocarcinoma with EGFR mutations. Issue 4 (22nd November 2019) - Hong, Guodai; Chen, Xuemei; Sun, Xizhuo; Zhou, Meiling; Liu, Bing; Li, Zhu; Yu, Zhendong; Gao, Wenbin; Liu, Tao
Abstract: This study investigated the efficiency of natural killer (NK) cell immunotherapy on non-small cell lung cancer with and without EGFR mutations in order to evaluate the response rate (RR) and progression-free survival (PFS). Among the 48 patients recruited, 24 were clinically confirmed to be EGFR mutation positive. The study group was treated with autologous NK cell immunotherapy. Comparisons of the lymphocyte number, serum tumour-related biomarkers, circulating tumour cells (CTC), Karnofsky Performance Status (KPS) and survival curves were carried out before and after NK cell immunotherapy. The safety and short-term effects were evaluated, followed by median PFS and RR assessments. The serum CEA and CA125 values were found lower in the NK cell therapy group than that of the non-NK treatment group ( p < 0.05 ). The χ 2 test showed a 75% RR of the study group A, significantly higher than that of the control group B (16.7%; p < 0.01 ). The RR of groups C (58.3%) and D (41.7%) were not statistically significant. The p values of the 4 groups were 0.012, 0.012, 0.166 and 1 from group A to group D, respectively. The median PFS was 9 months in EGFR mutation positive group undergoing NK cell infusion interference. By evaluating the changes in immune function, tumour biomarkers, CTC, KPS and PFS, we demonstrated that NK cell therapy had better clinical therapeutic effects on EGFR mutation-positive lung adenocarcinoma.